Xanthine oxidase activity exerts pro-oxidative and pro-inflammatory effects in serum of silver catfish fed with a diet contaminated with aflatoxin B1 - Baldissera M.D. (2018)
© 2018 John Wiley & Sons LtdSeveral studies have associated the involvement of xanthine oxidase (XO) activity, a source of uric acid and reactive oxygen species (ROS), to pro-oxidative and pro-inflammatory effects during pathological conditions. Considering this, the aim of this study was to evaluate whether upregulation on seric XO activity may be a pathway involved in the oxidative stress in fish exposed to a diet contaminated with aflatoxin B1 (AFB1), as well as whether it may be considered a pathway involved in ROS and NOx production. Xanthine oxidase activity, as well as the uric acid, ROS and NOx levels increased in serum of fish fed with a AFB1-contaminated diet on days 14 and 21 post-feeding compared to fish fed with a basal diet. Based on these evidences, upregulation of seric XO activity induces pro-oxidant and pro-inflammatory profiles in serum of fish fed with a AFB1-contaminated diet due to excessive formation on uric acid. Also, the excessive uric acid induces the release of pro-oxidant and pro-inflammatory mediators, as ROS and NOx, also contributing to oxidative and inflammatory profiles. In summary, the upregulation on seric XO activity may be considered a pathway involved in the oxidative stress of fish exposed to a diet contaminated with AFB1.